A solid dispersion of nilotinib hydrochloride, a solid preparation thereof, and a method for preparing the same
Patent Information
- Application Number
- CN202611172481.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-09-22
AI Technical Summary
[0010]本发明的内容是克服现有技术的不足,克服二元无增塑剂单一恒温挤出体系缺陷,解决醋酸羟丙甲纤维素琥珀酸酯(HPMCAS)热熔挤出时尼洛替尼高温降解杂质超标、低温无法形成无定型分散体、肠道稀释药物析晶、空腹生物利用度低、食物效应显著多重技术难题
1.处方层面:三元增塑剂热熔挤出固体分散体(盐酸尼洛替尼+HPMCAS+TEC或甘油三乙酯组合),三元增塑体系无需有机溶剂,绿色环保易产业化;杂质严格控制在单杂≤0.15%、总杂≤0.50%,远优于市场二元无增塑体系(市场多为仅二元药+载体,无增塑剂,熔体流动性差、局部过热杂质超标,储存易重结晶);加速储存无明显析晶,长期稳定性提升;通过添加合适量的增塑剂,降低熔体黏度,减少其在热熔挤出机中的滞留时间。同时,增塑剂的加入减少了输入的机械能,降低了杂质的生成。
Smart Images

Figure CN122786286A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of pharmaceutical technology, specifically relating to an amorphous solid dispersion of nilotinib hydrochloride, an oral solid dosage form containing the solid dispersion, and a segmented temperature-controlled hot melt extrusion preparation method thereof. Background Technology
[0002] Nilotinib hydrochloride, chemically named 4-methyl-N-[3-(4-methylimidazol-1-yl)-5-(trifluoromethyl)phenyl]-3-[(4-pyridin-3-ylpyrimidin-2-yl)amino]benzamide hydrochloride, has the following molecular formula and structural formula:
[0003] Nilotinib hydrochloride capsules, developed by Novartis, are a second-generation selective Bcr-Abl tyrosine kinase inhibitor, clinically marketed as Tasigna. It is primarily used for adult patients with Philadelphia chromosome-positive chronic myeloid leukemia (Ph+CML) in chronic or accelerated phase who are resistant to or intolerant of prior treatments (including imatinib). Nilotinib hydrochloride binds with high affinity to the ATP-binding site of Bcr-Abl kinase, potently inhibiting wild-type and most imatinib-resistant mutant Bcr-Abl proteins, blocking abnormal proliferation signals in leukemia cells and inducing tumor cell apoptosis. It also exhibits inhibitory activity against kinases such as c-Kit and PDGFR, making it a core first-line and second-line treatment for chronic myeloid leukemia.
[0004] The currently available mainstream dosage form is nilotinib hydrochloride capsules. The standard clinical dosage for newly diagnosed Ph+CML patients in the chronic phase is 300 mg twice daily, approximately 12 hours apart. For resistant or intolerant Ph+CML patients (chronic or accelerated phase), the dosage is 400 mg twice daily, approximately 12 hours apart. It should be taken at least 1 hour before or at least 2 hours after a meal. Nilotinib hydrochloride monohydrate belongs to the BCSIV class of drugs and has extremely low water solubility and low intestinal permeability: it is only slightly soluble in strongly acidic media and almost insoluble in the intestinal environment at pH ≥ 4.5. Its absolute oral bioavailability is only 30%, exhibiting a strong food effect; a high-fat diet can increase AUC by 82%, significantly increasing the risk of QT interval prolongation and arrhythmias. The drug instructions mandate strict fasting before and after administration, leading to poor patient compliance. Administration on an empty stomach can easily cause gastrointestinal adverse reactions. Nilotinib hydrochloride capsules rely solely on poloxamer for solubilization, resulting in slow dissolution and limited improvement in bioavailability. Furthermore, the large amount of surfactant poses long-term safety risks.
[0005] Solid dispersions are the mainstream technology for improving the dissolution of poorly soluble drugs. Solvent-based methods (spray drying, solvent precipitation) require large amounts of organic solvents such as dichloromethane and methanol, resulting in drawbacks such as solvent residue, high explosion-proof costs, poor batch stability, and easy crystallization during storage. Hot melt extrusion (HME) is a solvent-free, green process with significant industrialization advantages. Although impurities can be well controlled in spray drying, the dissolution rate is still relatively lower than that of hot melt extrusion (HME).
[0006] Existing technologies for preparing nilotinib solid dispersions via hot melt extrusion mostly employ single polymeric carriers such as hydroxypropyl methylcellulose succinate (HPMCAS), copovidone, or Soluplus. These technologies have significant drawbacks: the solubilizing ability of a single carrier in the molten state is limited; the amorphous system after extrusion is thermodynamically unstable and prone to recrystallization under accelerated storage conditions; some single polymeric carriers have narrow melting temperature windows, and high-temperature extrusion can easily lead to nilotinib degradation and an increase in related substances; furthermore, formulations prepared with single carriers still suffer from slow dissolution rates and unimproved food effects, failing to achieve the target of rapid high dissolution within 30 minutes.
[0007] CN108653223A provides a nilotinib tablet composition that solves the problem of decreased dissolution rate of nilotinib during stable storage, but it does not address the issue of nilotinib capsule administration. Among currently disclosed patents for the preparation of nilotinib solid dispersions, Shenzhen Taili Biopharmaceutical Co., Ltd.'s CN117100715A is a representative prior art. This patent mainly uses a spray drying process to prepare nilotinib solid dispersions. This mature process can achieve amorphous drug formation and effectively improve drug water solubility. However, this process relies on a large amount of organic solvent system, requiring specialized equipment for explosion-proof and solvent recovery systems. The production process is cumbersome, energy-intensive, and limited for large-scale industrial production, resulting in insufficient economic efficiency and convenience for mass production. Therefore, this invention develops a hot-melt extrusion preparation process suitable for industrial production, further optimizing product quality and production efficiency.
[0008] Meanwhile, the existing plasticizer-free hot-melt extrusion scheme for single hydroxypropyl methylcellulose succinate (HPMCAS) has obvious shortcomings: the maximum single impurity of the sample obtained by direct constant temperature extrusion at 190℃ is much greater than 0.20%, and the total impurity is much greater than 0.80%, which far exceeds the quality control limit of the formulation; if the temperature is simply reduced to 175℃ throughout the process, the drug cannot be completely melted, and an amorphous dispersion cannot be formed, resulting in substandard in vitro dissolution and an inability to balance impurity control and dissolution effect.
[0009] In summary, existing technologies lack technical solutions that can achieve low impurities, high dissolution, and high fasting bioavailability, and there is an urgent need to develop a nilotinib hydrochloride formulation technical solution. Summary of the Invention
[0010] The present invention aims to overcome the shortcomings of existing technologies and the defects of binary plasticizer-free single constant temperature extrusion systems, and to solve multiple technical problems during the hot melt extrusion of hydroxypropyl methylcellulose succinate (HPMCAS) nilotinib, such as excessive high-temperature degradation impurities, inability to form amorphous dispersions at low temperatures, drug crystallization due to intestinal dilution, low bioavailability on an empty stomach, and significant food effects.
[0011] This invention aims to provide a ternary solid dispersion containing nilotinib hydrochloride, hydroxypropyl methylcellulose acetate succinate (HPMCAS), and triethyl citrate (TEC) or triethyl glycerol as plasticizers. The plasticizers reduce melt viscosity, thus shortening residence time in the hot melt extruder. Simultaneously, the addition of plasticizers reduces the input mechanical energy, inhibiting degradation impurities at the source. A segmented temperature-controlled hot melt extrusion process is provided, characterized by high-temperature melting followed by low-temperature pressure stabilization. The initial high temperature ensures complete miscibility between the drug and carrier, forming an amorphous structure, while the subsequent cooling shortens the high-temperature residence time, balancing amorphous formation with impurity control.
[0012] To address the above problems, the technical solution provided by this invention is as follows: A nilotinib hydrochloride solid dispersion, said solid dispersion is prepared by hot melt extrusion co-melting of the active ingredient nilotinib hydrochloride, the carrier hydroxypropyl methylcellulose acetate succinate (HPMCAS) and a plasticizer; The plasticizer is one or both of triethyl glycerol or triethyl citrate.
[0013] Preferably, a nilotinib hydrochloride solid dispersion is prepared by twin-screw hot melt extrusion co-melting of nilotinib hydrochloride as the active ingredient, hydroxypropyl methylcellulose acetate succinate (HPMCAS) as the enteric carrier, and a plasticizer; wherein the plasticizer is any one of triethyl glycerol or triethyl citrate (TEC).
[0014] Preferably, a nilotinib hydrochloride solid dispersion is prepared by twin-screw hot melt extrusion co-melting of nilotinib hydrochloride as the active ingredient, hydroxypropyl methylcellulose acetate succinate (HPMCAS) as the enteric carrier, and triethyl glycerol as the plasticizer.
[0015] An oral solid dosage form of nilotinib hydrochloride, comprising the nilotinib hydrochloride solid dispersion, the oral solid dosage form further comprising an added micelle forming material, the added micelle forming material not participating in the hot melt extrusion process of the nilotinib hydrochloride solid dispersion, and the mass ratio of the added micelle forming material to nilotinib hydrochloride is 1~3:1.
[0016] The oral solid dosage form of nilotinib hydrochloride uses Soluplus or Eutrapeptide E100 as the micelle forming material. The oral solid dosage form of nilotinib is a tablet, capsule, granule, or dry suspension; preferably a tablet, which further comprises a filler, a disintegrant, and a lubricant.
[0017] A second aspect of the present invention provides a method for preparing a nilotinib hydrochloride solid dispersion, comprising the following steps: (1) Premixed soft material: Nilotinib hydrochloride and carrier hydroxypropyl methylcellulose succinate (HPMCAS) are put into a wet granulator and mixed evenly. The prescribed amount of plasticizer is sprayed in to obtain wet soft material. (2) Sieving and mixing: The wet soft material is repeatedly sieved through a 40-mesh sieve 3-5 times to obtain a uniform mixture; (3) Segmented temperature-controlled twin-screw hot melt extrusion: The homogeneous mixture is hot melt extruded using a five-zone twin-screw hot melt extruder, which includes zones one, two, three, four, and five. Zone one is the feeding and conveying zone, zone two is the melting zone, zone three is the melt-shear mixing zone, zone four is the melt-shear mixing zone, and zone five is the extrusion zone. The temperature of zone one is controlled at 12~18℃, the temperature of zone two is controlled at 115~125℃, the temperature of zones three and four is controlled at 180~190℃ during the initial melting stage, and the temperature of zone five is controlled at 145~160℃. The basic screw speed is 50~55 rpm, and the screw speed is gradually increased to 250~350 rpm after the material enters the extruder stably. rpm; After the extrudate in zone 5 turns into a yellow to dark yellow transparent or basically transparent melt, reduce the temperature of zones 3 and 4 to 170~185℃, keep the temperature of other zones unchanged, continue extrusion, discard the unstable extrudate in the first stage, and collect the subsequent light yellow to yellow transparent glassy extrudate.
[0018] (4) Crushing and sieving: The cooled extrudate is crushed in two stages. The first stage crushing removes coarse particles larger than 40 mesh, and the second stage crushing and sieving yields solid dispersion powder that meets the particle size requirements.
[0019] Preferably, the twin-screw extruder employs segmented temperature-controlled extrusion, characterized by high-temperature full melting and mixing followed by low-temperature stabilization and impurity control. The feeding and conveying zone in zone one is kept constant at 15°C, the melting zone in zone two is kept constant at 120°C, and the temperatures in zones three and four during the initial melting stage are 185°C. The screw's base speed is 50 rpm, and the screw is pre-washed for 3-5 minutes using copovidone, HPMCAS, or Soluplus. Feeding continues, and the screw speed is gradually increased to 300 rpm. After the extruded material from the die head transforms into a yellow to dark yellow transparent melt, the temperatures in zones three and four are reduced to 175°C, and the temperature in zone five is reduced to 155°C. Extrusion continues until the melt is a light yellow transparent glassy state. The waste material from the previous extrusion stage is discarded, and the qualified melt is collected. The extrusion process requires continuous and uninterrupted feeding and receiving.
[0020] Preferably, the particle size of the solid dispersion after secondary pulverization is controlled as follows: Dv10: 10~40μm, Dv50: 50~100μm, Dv90: 110~180μm; the impurity limit of the finished product is ≤0.15% for a single unknown impurity and ≤0.50% for total related substances.
[0021] The inventor discovered during the research process: 1. Using only the nilotinib hydrochloride + HPMCAS binary eutectic system without adding a special plasticizer will result in high melt viscosity, large heat generation from screw shear friction, severe degradation of nilotinib hydrochloride under heat, and difficulty in controlling total impurities and single impurities, which are very easy to exceed the standard. 2. The extrusion process is carried out at a single constant high temperature without segmented melting and then low-temperature stabilization. The drug is exposed to high temperature for a long time throughout the process, and impurities are continuously generated, which accelerates the increase of stability impurities. 3. Simply relying on amorphous solid dispersions to enhance initial dissolution may still result in drug precipitation during intestinal dilution, limiting the improvement in absorption on an empty stomach. Furthermore, adding micellar forming materials alone, without combining them with a solid dispersion system capable of enhancing initial dissolution and maintaining supersaturation, is insufficient to fully exert their solubilizing and supersaturation-maintaining effects. Therefore, this invention employs a combined strategy of "using amorphous solid dispersions to enhance initial dissolution and adding micellar forming materials to maintain supersaturation in intestinal fluid" to improve in vivo exposure under fasting conditions and help reduce absorption fluctuations caused by differences in gastrointestinal dissolution states.
[0022] The inventors compared three hot-melt carriers (polyvinylpyrrolidone VA64, a water-soluble polymer resin copolymerized from N-vinylpyrrolidone (NVP) and vinyl acetate (VA), produced by BASF; HPMCAS-L, hydroxypropyl methylcellulose acetate succinate, L-type, with acetyl substitution degree controlled ≤9%, produced by Shin-Etsu Chemical (Japan) or GM Chemical (India); and Soluplus, a polyvinylcaprolactam-polyvinyl acetate-polyethylene glycol graft copolymer, produced by BASF). Under the same process, the VA64 and Soluplus samples met the relevant substance impurities standards, but almost no dissolution occurred in the intestinal fluid medium at pH 6.8. Only the HPMCAS-L system achieved better dissolution, and the fasting pharmacokinetic Cmax and AUC of the canines were significantly better, but the binary system showed serious excessive impurities during high-temperature extrusion. The inventors unexpectedly discovered that adding a limited proportion of plasticizer triethyl glycerol or triethyl citrate (TEC) to the HPMCAS binary system can significantly reduce the melt glass transition temperature and screw torque, reduce heat generation from mechanical energy conversion, and significantly reduce related substances. However, if the plasticizer exceeds 15% of the carrier mass, the Tg will be too low, resulting in decreased storage stability and significantly reduced in vitro dissolution. Below 3%, there is no obvious impurity reduction effect. Therefore, the amount of plasticizer is limited to 3%~15% of the carrier mass.
[0023] The core of this invention is the segmented temperature-controlled extrusion mechanism: Extrusion at a single, continuous high temperature (e.g., 185°C) results in a continuously deepening melt color, increasing impurities with processing time, leading to high total impurities and failing to meet quality control standards. Extrusion at a single, continuous low temperature (e.g., 170-175°C) prevents complete melting of the drug, hindering the formation of a uniform amorphous structure and resulting in substandard dissolution. By utilizing the synergistic effect of the molten transparent melt on the unmelted material, the material is first fully melted and mixed at 185°C to obtain a transparent glassy state. Then, the overall temperature is lowered to 170-180°C for continuous extrusion, maintaining the melt in a transparent amorphous state. This significantly shortens the drug's heating time, resulting in a sample with a maximum unknown single impurity of less than 0.15% and total impurities of less than 0.50%, meeting internal impurity control limits.
[0024] After extrusion, the solid dispersion must be pulverized in two stages with strict particle size control: excessively large particle size reduces the dissolution rate; excessively small particle size easily leads to electrostatic agglomeration. The particle size ranges are defined as Dv10: 10~40μm, Dv50: 50~100μm, and Dv90: 110~180μm to ensure rapid dissolution.
[0025] The formulation lacks micelle excipients and relies solely on a single solubilization by the solid dispersion. This results in significant intestinal dilution and precipitation, leading to low fasting bioavailability and a pronounced food effect. To address the issue of intestinal supersaturation and crystallization after solid dispersion dissolution, this invention allows for the optional addition of micelle-forming excipients (Eutrapeptide E100, Soluplus) to the formulation. The micelle material does not participate in hot-melt extrusion but is only physically mixed. In vitro experiments have confirmed that Soluplus and Eutrapeptide E100 have the best inhibitory effect on crystallization. Fasting pharmacokinetic results in Beagle dogs showed that the AUC and Cmax of the formulation with added Soluplus were significantly higher than those with Eutrapeptide E100, and both were far superior to the control sample without added micelle material. A micelle material to API mass ratio of (1-3):1 can stably maintain intestinal drug supersaturation, improve fasting bioavailability, reduce the difference in fasting / postprandial blood drug concentration, and weaken the food effect.
[0026] Compared with the prior art, the present invention has the following advantages: 1. Formulation Level: Ternary plasticizer hot-melt extruded solid dispersion (nilotinib hydrochloride + HPMCAS + TEC or triethyl glycerol combination). The ternary plasticizer system requires no organic solvents, making it environmentally friendly and easy to industrialize. Impurities are strictly controlled to ≤0.15% for single impurities and ≤0.50% for total impurities, far superior to the market's binary unplasticized systems (most market systems are only binary drugs + carriers, without plasticizers, resulting in poor melt flowability, local overheating and excessive impurities, and easy recrystallization during storage). Accelerated storage shows no obvious crystallization, and long-term stability is improved. By adding an appropriate amount of plasticizer, the melt viscosity is reduced, shortening its residence time in the hot-melt extruder. At the same time, the addition of plasticizer reduces the input mechanical energy and reduces the formation of impurities.
[0027] 2. Process Level: The process employs a segmented temperature-controlled extrusion process, characterized by high-temperature melting followed by low-temperature pressure stabilization. This segmented temperature control addresses the dilemma of "high impurities at high temperatures and inability to form amorphous shapes at low temperatures," resulting in continuous and stable extrusion with high capacity and minimal batch-to-batch variation. The initial high-temperature stage achieves complete melting and mutual solubility to form amorphous shapes. The subsequent cooling stage shortens the high-temperature residence time of the drug while simultaneously preserving its transparent melt state, balancing both shaping and impurity control. Two-stage pulverization precisely controls particle size, ensuring rapid in vitro dissolution. 3. In vivo absorption: The addition of micelle-forming materials continuously maintains drug supersaturation, significantly increasing fasting AUC and Cmax, and significantly reducing the difference in blood drug concentration between fasting and postprandial administration, weakening the food effect, eliminating the need for strict fasting, and improving patient compliance; it can reduce the clinical dosage and reduce the risk of cardiotoxicity; the addition of micelle-forming materials to the formulation constructs a dual solubilization system, in situ encapsulating free nilotinib hydrochloride in intestinal fluid micelles, inhibiting dilution and crystallization, inhibiting intestinal P-gp efflux and transport, and improving fasting absorption.
[0028] 4. Industrialization advantages: The entire process is solvent-free, requiring no explosion-proof or solvent recovery equipment, resulting in lower production costs and strong feasibility for large-scale scaling. Attached Figure Description
[0029] Figure 1 The dissolution curves of the amorphous solid dispersions prepared in Examples 1-5 of this invention in a medium at pH 6.8; Figure 2 The dissolution curves of the amorphous solid dispersions prepared in Examples 6-8 of this invention in a medium at pH 6.8; Figure 3 The dissolution curves of the amorphous solid dispersions prepared in Examples 9-12 of this invention in a medium at pH 6.8 are shown. Figure 4 Dissolution profiles of three batches of the amorphous solid dispersion prepared in Example 13 of this invention were obtained in a medium at pH 6.8. Figure 5 Blood drug concentration-time curves for different samples administered orally to beagle dogs. The four groups of samples in the figure are the three batches of formulations prepared in Example 13 and the marketed product nilotinib capsules (trade name: Tasigna). The samples are represented by G1, G2, G3 and G4. G1: control formulation (capsule), G2: sample with Soluplus added, corresponding to formulation 3, G3: sample with Eucerin E100 added, corresponding to formulation 2, G4: sample without micelle material added, corresponding to formulation 1. Detailed Implementation
[0030] The following are detailed descriptions of embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0031] Preparation of amorphous solid dispersion of nilotinib hydrochloride The preparation process of Examples 1-5 is as follows: Nilotinib hydrochloride and extrusion carriers (HPMCAS-L, VA64, soluplus, etc.) are mixed in batches using a mixer.
[0032] Set up a hot melt extruder, and feed the above batches of materials through the feeding and conveying zone 1 at a constant temperature of 15°C, the melting zone 2 at a constant temperature of 120°C, and initially set the third and fourth zones to 185°C. The screw base speed is 50 rpm, and the screw is pre-washed with copovidone for 3-5 minutes. Then, add batches of materials and feed continuously while gradually increasing the screw speed to 300 rpm. The extrusion process must maintain continuous and uninterrupted feeding and receiving.
[0033] Comparison table of extrusion process parameters and properties for Examples 1-5: Table 1
[0034] The prepared amorphous solid dispersion was tested for relevant substances.
[0035] List of impurity spectra for Examples 1-5: Table 2
[0036] Dissolution behavior Dissolution experiments were conducted on the amorphous solid dispersions prepared in Examples 1-5. The dissolution curves (pH 6.8 medium) are shown below. Figure 1 As shown.
[0037] Experimental results showed that the related substances in Examples 4 and 5 were good, but there was basically no dissolution. In Examples 1, 2 and 3, the impurities in the single high-temperature extrusion without plasticizer were seriously excessive and could not meet the quality control requirements of the formulation, but the dissolution rate at 30 minutes was 75%-90%.
[0038] Preparation of amorphous solid dispersion of nilotinib hydrochloride The preparation process of Examples 6-8 is as follows: Nilotinib hydrochloride and HPMCAS-L were mixed evenly in a wet granulator, and then 10% triethyl glycerol was slowly sprayed in at the prescribed amount to obtain a wet soft mass. The wet soft material was repeatedly passed through a 40-mesh sieve three times to obtain a homogeneous mixture. The twin-screw extruder employs zoned gradient temperature control. Material is fed into a constant temperature zone (15°C) in the first feeding and conveying zone, and into a constant temperature zone (120°C) in the second melting zone. Initially, zones three and four are set to 185°C, with a base screw speed of 50 rpm. The screw is pre-washed with copovidone for 3-5 minutes. Then, material is continuously fed in, and the screw speed is gradually increased to 300 rpm. Continuous feeding and receiving are required throughout the extrusion process. After the extruded material from the die transforms into a yellow to deep yellow transparent melt, samples are taken for testing using three temperature control methods: ① constant 185°C; ② constant 175°C; ③ first raising the temperature to 185°C until transparent extrusion for 3-5 minutes, then lowering it to 175°C for constant extrusion. All three extrusion methods are followed until the melt is a light yellow, transparent glassy state. The qualified melt is collected after discarding the waste material from the initial extrusion stage.
[0039] Comparison table of extrusion process parameters and properties for Examples 6-8: Table 3
[0040] The prepared amorphous solid dispersion was tested for relevant substances.
[0041] List of impurity spectra in Examples 6-8: Table 4
[0042] Dissolution behavior Dissolution experiments were conducted on the amorphous solid dispersions prepared in Examples 6-8. The dissolution curves (pH 6.8 medium) are shown below. Figure 2 As shown.
[0043] Experimental results show that in Example 6, the unknown single impurities in the related substances of the extruded solid dispersion at a constant high temperature of 185°C exceeded the limit. In Example 7, the single impurities and total impurities in the related substances of the extruded solid dispersion at a constant relative low temperature of 175°C met the limit, but the appearance was semi-transparent, posing a great risk of not being completely amorphous and also posing a significant risk to the later stability process. In Example 8, the solid dispersion was first extruded at 185°C until transparent for 3-5 minutes, and then extruded at a constant temperature of 175°C. The single impurities and total impurities in the related substances met the limit, and the appearance was transparent, which was relatively better. The dissolution was basically equivalent to that of Example 6 and Example 7.
[0044] Preparation of amorphous solid dispersion of nilotinib hydrochloride The preparation process of Examples 9-12 is as follows: Nilotinib hydrochloride and HPMCAS-L were mixed evenly in a wet granulator to prepare four batches. 5% TEC, 10% TEC, 5% triethyl glycerol and 10% triethyl glycerol were slowly sprayed into each batch to obtain wet soft material. The wet soft material was repeatedly passed through a 40-mesh sieve three times in batches to obtain a homogeneous mixture. The twin-screw extruder employs zoned gradient temperature control. Batch materials are fed through a constant temperature of 15°C in zone one (feeding and conveying), and a constant temperature of 120°C in zone two (melting). Initially, zones three and four are set at 185°C, with a base screw speed of 50 rpm. The screw is pre-washed with copovidone for 3-5 minutes. Then, batch materials are continuously fed in, and the screw speed is gradually increased to 300 rpm. Continuous feeding and receiving are required throughout the extrusion process. After the extruded material from the die transforms into a yellow to deep yellow transparent melt, samples of all four batches of the mixture are taken for testing using the same temperature control method: first, the temperature is raised to 185°C until transparent extrusion is achieved for 3-5 minutes, then lowered to a constant temperature of 175°C until extrusion ends. All four batches of extrudate are extruded until the melt is a light yellow, transparent glassy state. The qualified melt is collected after discarding the waste material from the initial extrusion stage.
[0045] Comparison table of extrusion process parameters and properties for Examples 9-12: Table 5
[0046] The prepared amorphous solid dispersion was tested for relevant substances.
[0047] List of impurity spectra in Examples 9-12: Table 6
[0048] Dissolution behavior Dissolution experiments were conducted on the amorphous solid dispersions prepared in Examples 9-12. The dissolution curves (pH 6.8 medium) are shown below. Figure 3 As shown.
[0049] Experimental results show that the solid dispersions extruded in Examples 9-12 all meet the limits for both single impurities and total impurities, with Example 12 being the best relative to related substances. All solid dispersions were light yellow and transparent, with dissolution rates ranging from 80% to 90%, although Example 12 showed a slightly higher rate overall.
[0050] Preparation of Nilotinib Hydrochloride Amorphous Solid Dispersion and Formulation The preparation process of Example 13 is as follows: Nilotinib hydrochloride and HPMCAS-L were mixed evenly in a wet granulator, and 10% triethyl glycerol was sprayed in at the prescribed amount to obtain wet soft material. The wet soft material was repeatedly passed through a 40-mesh sieve three times in batches to obtain a homogeneous mixture. The twin-screw extruder employs zoned gradient temperature control. Material is fed in zone one at a constant temperature of 15°C, and in zone two at a constant temperature of 120°C. Initially, zones three and four are set at 185°C, with a base screw speed of 50 rpm. The screw is pre-washed with copovidone for 3-5 minutes. Then, batches of material are continuously fed, and the screw speed is gradually increased to 300 rpm. Continuous feeding and receiving are required throughout the extrusion process. After the extruded material from the die transforms into a yellow to deep yellow transparent melt, the mixture undergoes segmented temperature-controlled extrusion: first, high-temperature full melting and mutual solubility, followed by low-temperature stable pressure and impurity control. The temperature is first raised to 185°C for transparent extrusion for 3-5 minutes, then lowered to a constant 175°C to end the extrusion. The extrudate is extruded until the melt is a light yellow transparent glassy state. The waste material from the first extrusion stage is discarded, and the qualified melt is collected. Example 13: Comparison of extrusion process parameters and properties. Table 7
[0051] The cooled extrudate is subjected to two-stage pulverization. The first-stage pulverization removes coarse particles larger than 40 mesh, and the second-stage pulverization is followed by sieving to obtain a solid dispersion powder that meets the particle size requirements. The particle size of the solid dispersion after pulverization is controlled as follows: Dv10: 10~40μm, Dv50: 50~100μm, Dv90: 110~180μm.
[0052] The prepared solid dispersions were divided into three sub-batches. Formulas 1, 2 and 3 were all prepared using the solid dispersion sub-batches prepared in Example 13 and were prepared into finished tablets according to the table below.
[0053] Table 8
[0054] Process steps Granulation process: The amorphous solid dispersion, microcrystalline cellulose colloidal silica co-treated product, lactose, crospovidone, behenicol glyceryl ester, and external polymer (no polymer in prescription 1, E100 in prescription 2, and Soluplus in prescription 3) are added to a mobile granulator for granulation. The granulation screen is 1.2mm and the granulation speed is 500rpm.
[0055] The final mixing process: The three batches of granulated particles are mixed separately in a hopper mixer at a stirring speed of 15 rpm for 20 minutes to obtain the final mixed particles.
[0056] Tableting process: The three batches of total mixed granules are compressed into tablets using a rotary tablet press to obtain the finished product, with the hardness controlled at around 200N.
[0057] Dissolution behavior The amorphous solid dispersion prepared in Example 13 was used to prepare three batches of formulations for dissolution experiments. The dissolution curves (pH 6.8 medium) are shown below. Figure 4 As shown.
[0058] Experimental results showed that the dissolution rates of formulations 2 and 3 with added polymers (E100 and soluplus) were both higher than that of formulation 1 without micelles. The dissolution rates of formulations 2 and 3 were essentially equivalent.
[0059] Animal pharmacokinetic evaluation was conducted using three batches of formulations prepared in Example 13 and the marketed product nilotinib capsules (trade name: Tasigna). The four sample groups were designated G1, G2, G3, and G4, respectively. G1: control formulation (capsules); G2: sample with Soluplus added, corresponding to formulation 3; G3: sample with Eucerin E100 added, corresponding to formulation 2; and G4: sample without micellar material added, corresponding to formulation 1. Specific animal experimental data are shown in the table below. Figure 5 : Table 9
[0060] Experimental results showed that the mean pharmacokinetic parameters (T / R) of the test formulation and the control formulation (commercially available nilotinib capsules G1) were as follows: The fasting Cmax and AUC of the nilotinib hydrochloride solid dispersion (Formulation 1, G4) without micellar solubilizing carriers were also significantly higher. 0-t AUC 0-∞ The bioavailability of nilotinib hydrochloride solid dispersion (Formulation 2, G3) was 144.30%, 131.53%, and 121.03% of that of commercially available nilotinib capsules (G1), respectively, with a relative bioavailability of 121%. These results suggest that amorphous solid dispersion formulations alone can improve the initial dissolution behavior of nilotinib, but the overall in vivo exposure under fasting conditions is only slightly higher than that of commercially available capsules, indicating that the improvement in in vivo absorption by relying solely on solid dispersion systems is limited. The Cmax and AUC of nilotinib hydrochloride solid dispersion (Formulation 2, G3) with the addition of Etotifen E100 were also compared under fasting conditions. 0-t AUC 0-∞ The bioavailability of nilotinib hydrochloride was 140.92%, 190.57%, and 146.70% of that of commercially available nilotinib capsules (G1), with a relative bioavailability of 146%. These results suggest that the addition of E100 can further improve the in vivo absorption of nilotinib hydrochloride under fasting conditions, resulting in a significantly higher overall exposure level compared to the formulation without the added material. The Cmax and AUC of the nilotinib hydrochloride solid dispersion formulation (Formulation 3, G2) with Solplus added material after fasting administration were also compared. 0-t AUC 0-∞The bioavailability of Soluplus was 327.80%, 294.39%, and 310.50% of that of commercially available nilotinib capsules (G1), respectively, with a relative bioavailability of 311%. Soluplus, as a micelle-forming material, exhibited extremely strong solubilizing and absorption-enhancing capabilities, which could significantly improve the in vivo exposure of nilotinib hydrochloride under fasting conditions. This suggests that when this material is combined with the amorphous solid dispersion of nilotinib hydrochloride, it can further improve the drug's solubilizing and supersaturation maintenance capabilities in the gastrointestinal environment. It also further suggests that the formulation of this invention has the development potential to achieve the target exposure by reducing the dosage.
[0061] A comprehensive comparison of prescriptions 1, 2, and 3 shows that the overall exposure of nilotinib hydrochloride amorphous solid dispersion alone under fasting conditions is only slightly improved compared to commercially available capsules; with the addition of E100, the AUC... 0-t and AUC 0-∞ Compared to formulation 1, the absorption rate was improved; with the addition of Soluplus, both Cmax and AUC increased significantly, indicating a stronger absorption-enhancing effect. These results demonstrate that the present invention, by combining "improving initial dissolution with amorphous solid dispersions" with "maintaining drug solubility and supersaturation with added micellar forming materials," can effectively improve the in vivo absorption of nilotinib hydrochloride under fasting conditions.
[0062] The scope of protection of this invention is not limited to the specific embodiments described above. The terminology used in the embodiments is for describing specific embodiments and not for limiting the scope of protection of this invention. Test methods not specified in the embodiments are generally performed under conventional conditions or methods commonly known to those skilled in the art.
Claims
1. A nilotinib hydrochloride solid dispersion, characterized in that, The solid dispersion was prepared by hot melt extrusion co-melting of the active ingredient nilotinib hydrochloride, the carrier hydroxypropyl methylcellulose acetate succinate, and the plasticizer. The plasticizer is one or both of triethyl glycerol or triethyl citrate.
2. The solid dispersion as described in claim 1, characterized in that, The mass ratio of nilotinib hydrochloride, hydroxypropyl methylcellulose acetate succinate, and plasticizer is 1:(3~5):(0.09~0.75).
3. The solid dispersion as described in claim 2, characterized in that, The amount of plasticizer added is 3% to 15% of the total mass of the carrier.
4. The solid dispersion as described in claim 1, characterized in that, The hydroxypropyl methylcellulose acetate succinate, model HPMCAS-L, has an acetyl substitution degree ≤9%.
5. The solid dispersion as described in claim 1, characterized in that, The nilotinib hydrochloride solid dispersion is an amorphous solid dispersion.
6. The solid dispersion as described in claim 1, characterized in that, The solid dispersion is prepared by co-melting of the active ingredient nilotinib hydrochloride, the carrier hydroxypropyl methylcellulose acetate succinate, and the plasticizer via twin-screw hot melt extrusion.
7. The method for preparing nilotinib hydrochloride solid dispersion according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Premixed soft material: Nilotinib hydrochloride and the carrier hydroxypropyl methylcellulose succinate are put into a wet granulator and mixed evenly. The prescribed amount of plasticizer is sprayed in to obtain wet soft material. (2) Sieving and mixing: The wet soft material is repeatedly sieved through a 40-mesh sieve 3-5 times to obtain a uniform mixture; (3) Segmented temperature-controlled twin-screw hot melt extrusion: The homogeneous mixture is hot melt extruded using a five-zone twin-screw hot melt extruder, which includes zones one, two, three, four, and five. Zone one is the feeding and conveying zone, zone two is the melting zone, zone three is the melt-shear mixing zone, zone four is the melt-shear mixing zone, and zone five is the extrusion zone. The temperature of zone one is controlled at 12~18℃, the temperature of zone two is controlled at 115~125℃, the temperature of zones three and four is controlled at 180~190℃ during the initial melting stage, and the temperature of zone five is controlled at 145~160℃. The basic screw speed is 50~55 rpm, and the screw speed is gradually increased to 250~350 rpm after the material enters the extruder stably. rpm; After the extrudate in zone 5 turns into a yellow to dark yellow transparent or basically transparent melt, reduce the temperature of zones 3 and 4 to 170~185℃, while keeping the temperature of other zones unchanged, continue extruding and collect the light yellow to yellow transparent glassy extrudate; (4) Crushing and sieving: The cooled extrudate is crushed in two stages and then sieved to obtain a solid dispersion powder that meets the particle size requirements.
8. The preparation method according to claim 7, characterized in that, The twin-screw extruder adopts segmented temperature-controlled extrusion, which first achieves full melting and dissolution at high temperature and then stabilizes and controls impurities at low temperature. The feeding and conveying zone in zone one is kept at a constant temperature of 15°C, the melting zone in zone two is kept at a constant temperature of 120°C, and the temperature in zones three and four is 185°C during the start-up melting stage.
9. The preparation method according to claim 8, characterized in that, The particle size after pulverization is controlled as follows: Dv10: 10~40μm, Dv50: 50~100μm, Dv90: 110~180μm; the impurity limit of the finished product is ≤0.15% for a single unknown impurity and ≤0.50% for total related substances.
10. A nilotinib hydrochloride oral solid dosage form, characterized in that, The oral solid dosage form comprises the nilotinib hydrochloride solid dispersion according to any one of claims 1-6, or the nilotinib hydrochloride solid dispersion prepared by the preparation method according to any one of claims 7-9; the oral solid dosage form further comprises an external micelle forming material, the external micelle forming material not participating in the hot melt extrusion process of the nilotinib hydrochloride solid dispersion, and the mass ratio of the external micelle forming material to nilotinib hydrochloride is 1 to 3:
1.
11. The nilotinib hydrochloride oral solid dosage form according to claim 10, characterized in that, The micelle forming material is Soluplus or Utex E100.
12. The nilotinib oral solid dosage form as described in claim 10 or 11, characterized in that, The oral solid dosage form is a tablet, capsule, granule, or dry suspension.
Citation Information
Patent Citations
Nilotinib tablet composition
CN108653223A
Capsule containing amorphous nilotinib and preparation method thereof
CN117100715A